O método APAC como gestão penitenciária comunitária e a promoção das funções da pena de prisão - Nascimento, Beatriz Cunha do (2016)
The purpose of this research is to analyze the APAC method of enforcement of sentence of imprisonment, with the aim of understanding the links between the prison health care treatment of the prisoner and their consistency with the principles of human dignity and the exercise of fundamental rights advocated by the Federal Constitution of 1988. Therefore, it was performed a preliminary study about the functions of the deprivation of freedom to demonstrate that despite the Brazilian legal system to adopt the mixed theory that would desired punishment, prevention and rehabilitation of the convict, the current purpose of prison is none other than punitive. Next, it was performed a brief analysis of the effectiveness of the rights and guarantees of the citizen convicted, from the perspective of warranty theory Luigi Ferrajoli, which strives for limiting punitive intervention in a democratic state, based on respect for human dignity. Finally, it is made some consideration on the APAC method of humanization of the prison system and effectiveness of fundamental rights envisaged in the constitutional normative text, apply the Social Reintegration Centers, whose main characteristic is the absence of weapons or armed guards in guarding the prisoners, and the same held by them detainees. That said, it should be noted that had been used the inductive method by qualitative descriptive research, exploring the theme from bibliographic means in order to understand the peculiarities of the subject that has been studied.